2014
DOI: 10.1371/journal.pone.0098439
|View full text |Cite
|
Sign up to set email alerts
|

Speech Sound Processing Deficits and Training-Induced Neural Plasticity in Rats with Dyslexia Gene Knockdown

Abstract: In utero RNAi of the dyslexia-associated gene Kiaa0319 in rats (KIA-) degrades cortical responses to speech sounds and increases trial-by-trial variability in onset latency. We tested the hypothesis that KIA- rats would be impaired at speech sound discrimination. KIA- rats needed twice as much training in quiet conditions to perform at control levels and remained impaired at several speech tasks. Focused training using truncated speech sounds was able to normalize speech discrimination in quiet and background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 96 publications
3
24
1
Order By: Relevance
“…These animals do not show the expected migration deficits, and lack lamination defects or clear anomalies in the cortex; however, changes in learning, memory or auditory processing have been reported in both cases (Gabel et al 2011; Truong et al 2014; Rendall et al 2015). Similarly, in utero knockdown of Kiaa0319 in the embryonic rat cortex leads to spatial learning deficits and affect responses to complex acoustic stimuli (Szalkowski et al 2012; Centanni et al 2014a, b). We, therefore, decided to perform a general behavioural characterisation of the Kiaa0319 mutant animals to elucidate functional effects of Kiaa0319 knockout and conducted a standard series of mouse behavioural tests on a cohort of control and mutant mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These animals do not show the expected migration deficits, and lack lamination defects or clear anomalies in the cortex; however, changes in learning, memory or auditory processing have been reported in both cases (Gabel et al 2011; Truong et al 2014; Rendall et al 2015). Similarly, in utero knockdown of Kiaa0319 in the embryonic rat cortex leads to spatial learning deficits and affect responses to complex acoustic stimuli (Szalkowski et al 2012; Centanni et al 2014a, b). We, therefore, decided to perform a general behavioural characterisation of the Kiaa0319 mutant animals to elucidate functional effects of Kiaa0319 knockout and conducted a standard series of mouse behavioural tests on a cohort of control and mutant mice.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted with rats following in utero electroporation to knockdown Kiaa0319 (Szalkowski et al 2012; Centanni et al 2014a, b) have reported spatial learning deficits and impaired auditory processing but normal working memory using behavioural and electrophysiological tests. In the particular case of spatial learning, when assessed using the Morris water maze, these deficits were found only in animals showing also hippocampal anatomical malformations (Szalkowski et al 2012), suggesting a direct relationship between anatomical and behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that experimental interference of the dyslexia susceptibility genes in rodents causes atypical neuronal migration, which in turn results in localized matter malformations that affect cortical circuitry [16,17]. For example, in utero disruption of KIAA0319 expression in rats has been shown to result in poor neural representation of speech sounds in the auditory cortex and in impaired performance on phoneme discrimination tasks [18 • ,19,20]. The reported behavioral impairments in these animal studies are similar to those observed in individuals diagnosed with dyslexia [e.g., 21], especially those who showed KIAA0319 and DCDC2 variants [22].…”
Section: Genetics and The Neurobiology Of Dyslexiamentioning
confidence: 99%
“…The FFR is thought to predominantly reflect activity in the auditory midbrain that faithfully captures the encoding of acoustic characteristics of speech sounds (Chandrasekaran & Kraus, 2010; White-Schwoch, Nicol, Warrier, Abrams, & Kraus, 2016) with recent evidence also suggesting a contribution from auditory cortex (Coffey, Herholz, Chepesiuk, Baillet, & Zatorre, 2016). Apart from capturing the acoustic characteristics of speech sounds, the FFR can also be examined in terms of its neural stability, capturing how consistently an individual’s brain responds to speech sounds (Centanni, Engineer, & Kilgard, 2013; Centanni et al, 2014; Hornickel & Kraus, 2013). Neural stability has often been associated with children’s reading ability (Hornickel & Kraus, 2013; White-Schwoch et al, 2015), with poor readers showing more variable FFR.…”
Section: Introductionmentioning
confidence: 99%